2000
DOI: 10.1038/sj.jhh.1001127
|View full text |Cite
|
Sign up to set email alerts
|

Why is plasma renin activity lower in populations of African origin?

Abstract: Plasma renin activity is significantly lower in black people compared with whites independent of age and blood pressure status. The lower PRA appears to be due to a reduction in the rate of secretion of renin but the exact mechanistic events underlying such differences in renin release between blacks and whites are still not fully understood. Nevertheless, given the paramount importance of the renin-angiotensin system in the control of sodium balance, a most likely explanation is that the lower renin is a cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
58
0
5

Year Published

2003
2003
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(65 citation statements)
references
References 70 publications
(92 reference statements)
2
58
0
5
Order By: Relevance
“…Our recent data indicate that impaired SIPN is approximately twice as prevalent in black as in white youth (40% versus 20%) (Harshfield et al, Annual Meeting of Society of Behavioral Medicine, April 13-16, 2005, Boston). The genetic and environmental determinants of salt sensitivity and pressure natriuresis are speculated to be race-related (25).…”
Section: Grk4 Gene and Sodium Excretionmentioning
confidence: 99%
“…Our recent data indicate that impaired SIPN is approximately twice as prevalent in black as in white youth (40% versus 20%) (Harshfield et al, Annual Meeting of Society of Behavioral Medicine, April 13-16, 2005, Boston). The genetic and environmental determinants of salt sensitivity and pressure natriuresis are speculated to be race-related (25).…”
Section: Grk4 Gene and Sodium Excretionmentioning
confidence: 99%
“…In our total HyperPATH cohort study, we confirmed that ALDO, PRA, and potassium levels on a LIB salt diet were lower in AD than ED, as has been shown by others (1)(2)(3)(4)(5)(6)24). Because of limited genotyping data, we also performed analyses in a 2:1 restricted subcohort.…”
Section: Discussionmentioning
confidence: 55%
“…Compared with persons of European descent (ED), individuals of African descent (AD) are known to: (i) be more susceptible to cardiovascular disease (CVD); (ii) have a greater frequency of hypertension (HTN) (particularly salt-sensitive HTN); (iii) have more cardiovascular (CV) damage with HTN; (iv) have lower plasma renin activity (PRA); and (v) more resistant HTN (1)(2)(3)(4)(5)(6). Of interest, these same characteristics also are associated with increased aldosterone (ALDO) production, e.g., primary aldosteronism.…”
Section: Introductionmentioning
confidence: 99%
“…Black patients have low renin activity [5] coupled with lower aldosterone [6]. On the other hand, there is an excessive RAAS system-dependent target organ damage in black hypertensive patients.…”
Section: Hypertension In Patients With African Ancestrymentioning
confidence: 99%